An Introduction of Gorkha Museum: A Collection of Ancient Treasure (The Educator Journal, 2022)
This article gives a detailed introduction to Gorkha Museum. It has been developed based on the Museum’s monumental and historical treasures stored and exhibited. The narratives from the Chief and the staff of Gorkha Museum helped the author give the Museum’s details. Secondary sources of information have been utilized to develop this write-up. The main aim of this article is to shed light on Gorkha Museum. The readers can get detailed information on the treasures exhibited at the Museum. Gorkha Museum has a collection of historical documents, colophons, oil portraits, traditional musical instruments, weapons, Chaityas, utensils and other sources immensely valuable for providing information and knowledge required in the field of politics, religion, culture, art, literature and architecture of Gorkha from ancient to the modern. Moreover, documents exhibited at the Museum reflect both internal and foreign relations during the Shah rulers (from Dravya Shah to Prithvi Narayan Shah). The Museum, thus, is worth visiting for research scholars, academics and politicians too for enhancing their knowledge of the then Gorkha as a whole.